Karakterisasi Genetik Fragmen Gen Penyandi RNA Polimerase Infectious Myonecrosis Virus (IMNV) yang Menginfeksi Udang Vannamei (Litopenaeus vannamei Boone.) dari Lampung, Gresik dan Pontianak - Sudjito, Yason Lukman; Handayani, Christina Retna; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto (Bioma : Berkala Ilmiah Biologi, 2014)
A massive death of vannamei shrimp (Litopenaeus vannamei Boone.) due to Infectious Myonecrosis Virus (IMNV) infection has occurred in Indonesia recently and still cannot be eradicated efficiently. The fast reproduction of IMNV depends on the RdRp gene that encodes for RNA polymerase. Genetic characterization of IMNV RdRp gene from Indonesia is important in order to compare with other IMNV to find out genetic variation as a base for combating this virus. IMNV-infected vannamei were taken from major aquaculture region in Indonesia (Lampung, Gresik and Pontianak). RNA polymerase coding genes (12 and 13 region) from infected vannamei were amplified using RT-PCR with appropriate primer. Amplification products were sequenced and the results were analyzed using BioEdit 7.1.3.0, ClustalW2, CLC free workbench 6.6.2. and ClustalX programs. Results showed that homology value of IMNV RdRp gene  from Lampung and Gresik were 98,04-9958% compared with IMNV from Brazil (Acc. No. AY570982). Amino acid analysis revealed homology value of IMNV RdRp gene  from Lampung  and Gresik were 100% and 99.04% compared with IMNV from Brasil. IMNV RdRp gene  from Pontianak cannot be analysed due to low quality of RNA.   Key words: vannamei, IMNV, RdRp, genetic characterization